2007
DOI: 10.1007/s00467-006-0408-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carnitine supplementation on lipid profile and anemia in children on chronic dialysis

Abstract: We prospectively evaluated the effects of Lcarnitine supplementation on plasma free carnitine (FC) levels, serum lipid profile, and erythropoietin (rhEPO) requirement in 24 children treated with peritoneal dialysis (PD; n=16) or hemodialysis (HD; n=8). The study was divided into a 3-month observation period, and a 3-month treatment period during which patients received 20 mg/kg per day of L-carnitine given orally. Clinical, biochemical, and hematological data were collected every 3 months. FC levels were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
(41 reference statements)
1
18
1
Order By: Relevance
“…However, our study design does not definitively exclude the possibility that other parameters may have played a role in this result, as a control group was missing. This result stands in contrast to a study carried out by Verrina et al [8] that b Erythropoetin requirement before and at the end of the L-carnitine supplementation. Patients with a higher EPO dose had a relatively higher benefit in terms of EPO dose reduction showed no effect of L-carnitine on hematological parameters.…”
Section: Discussioncontrasting
confidence: 85%
“…However, our study design does not definitively exclude the possibility that other parameters may have played a role in this result, as a control group was missing. This result stands in contrast to a study carried out by Verrina et al [8] that b Erythropoetin requirement before and at the end of the L-carnitine supplementation. Patients with a higher EPO dose had a relatively higher benefit in terms of EPO dose reduction showed no effect of L-carnitine on hematological parameters.…”
Section: Discussioncontrasting
confidence: 85%
“…[481][482][483][484] Far less information pertaining to the relationship between dialysis and carnitine deficiency is available from the PD population. 485,486 Carnitine deficiency can result in the development of anemia, cardiomyopathy, and muscle weakness, all symptoms that may be present in the dialysis population. 481,482,487,488 It is also associated with intradialytic hypotension in patients receiving HD.…”
Section: Rationalementioning
confidence: 99%
“…However, studies addressing the therapeutic use of supplemental Lcarnitine in dialysis patients are few and have characteristically included small numbers of patients. 485,486,489,490 This has compromised any ability to generate definitive evidence supporting the role of regular supplemental L-carnitine in the treatment of these symptoms. Along these lines, the KDOQI Adult and Pediatric Work Group on Anemia Management conducted a thorough evaluation of the data particular to the treatment of anemia in patients with CKD and concluded there was insufficient evidence to recommend a role for carnitine in the treatment of anemia.…”
Section: Rationalementioning
confidence: 99%
“…In two additional randomized, controlled trials in which anemia and epoetin dosing were not primary endpoints, intravenous LC administration was not associated with significant changes in hemoglobin or epoetin dose from baseline or compared with a control group (20,21). Trials of oral LC in adults (22) and children (23) showed no change in hemoglobin level after 3 (23) or 6 (22) months.…”
Section: Lc Stimulates Erythropoiesis In Mouse Bonementioning
confidence: 99%